Management of elderly patients with sustained hypertension. Issue 6824 (15th February 1992) - Beard, K.; Bulpitt, C.; Mascie-Taylor, H.; O'Malley, K.; Sever, P.; Webb, S.
Abstract : OBJECTIVE–To assess the clinical benefits of treating hypertension in elderly patients and to derive practical guidelines regarding indications, goals, and forms of treatment. DESIGN–Review of six published randomised trials. RESULTS–Active treatment of hypertension in elderly patients was associated with significant improvements in several indices of cardiovascular morbidity and mortality, particularly the incidence of fatal and non-fatal strokes. On the basis of the trial data, combined systolic and diastolic hypertension was defined as a sustained systolic pressure greater than 160 mmHg and diastolic pressure greater than 90 mmHg. There is convincing evidence that efforts should be made to reduce both systolic and diastolic pressures to below these levels in patients up to the age of 80 years. Isolated systolic hypertension was defined as a systolic pressure greater than 160 mmHg in the presence of a diastolic pressure less than 90 mmHg. Two trials reported benefit from the treatment of isolated systolic hypertension in patients up to the age of 80, and further trials are underway to support or refute this recommendation. Diuretics have an established role in the management of hypertension in elderly patients; beta adrenoceptor antagonists have given variable results, and the benefits are less impressive than with diuretic based regimens. Newer agents show promise in the treatment of elderly patients, particularly in the presence of coexisting disease, but their effects on morbidity and mortality have not been evaluated in large randomised trials. CONCLUSIONS–Diuretics rather than beta blockers are the treatment of choice for patients with uncomplicated hypertension, but combinations of drugs may be required in as many as 50% of patients.